Robust Superhydrophobic/Superoleophilic Wrinkled Microspherical MOF@rGO Composites for Efficient Oil–Water Separation. Issue 16 (6th February 2019) - Gu, Jiahui; Fan, Hongwei; Li, Chunxi; Caro, Jürgen; Meng, Hong
Abstract: Graphene/MOF‐based composite materials in three‐dimensional (3D) architectures are promising for the treatment of oil‐containing wastewater by absorption owing to their intrinsic properties of graphene and metal‐organic frameworks (MOFs), such as high porosity, ultralow density, and facilely tailored superwettability. In this study, novel wrinkled 3D microspherical MOF@rGO composites with both superhydrophobic and superoleophilic properties were developed by embedding MOF nanoparticles between graphene oxide (GO) nanosheets, followed by high‐temperature reduction self‐assembly. The microspherical composites feature a unique micro/nano hierarchy consisting of crumpled reduced GO (rGO) nanosheets intercalated with well‐dispersed MOF nanoparticles. Combined with the superwettability and abundant meso/microporosity, the peculiar architectures of wrinkled ZIF‐8@rGO microspheres show very fast absorption rates and high sorption selectivity for organic solvents and oils from water. Abstract : Simply super ! Wrinkled ZIF‐8@rGO microspheres consisting of crumpled reduced graphene oxide (rGO) nanosheets intercalated with well‐dispersed ZIF‐8 nanoparticles were prepared as a superhydrophobic/superoleophilic material. A ZIF‐8@rGO@Sponge adsorbent prepared from this material by using a commercial sponge showed excellent oil–water separation performance (see picture) and good recyclability.